Qualificação dos registros de procedimentos em centros de atenção psicossocial: educação permanente em saúde como estratégia de gestão - Silva, Nathália dos Santos (2018)
The Psychosocial Care Centers (CAPS) are strategic services of the Psychosocial Care Network to promote the social reintegration of people with mental disorders and or problems related to the use of alcohol and other drugs. Thus, it is imperative that the actions in the CAPS be monitored and evidenced to support the superiority of this proposal. However, this will only be possible if there are data recorded by the professionals working in the CAPS to enable the evaluation for the management of the quality of the services. This study aimed to analyze the quality of records of procedures using the Permanent Education in Health as a strategy for the management of the work process of the health professionals of the CAPS. This is an intervention research of a qualitative nature, carried out with 58 professionals from seven CAPS from three municipalities of the State of Goiás. Data collection occurred from March to October 2016. The Permanent Health Education was procedural and occurred in three stages: focus groups, seminars and workshops on CAPS procedures and elaboration of a Unique Therapeutic Project (PTS). With the data obtained through the reflection of the subjects, the thematic content analysis was performed. The thematic categories and subcategories that emerged from the content analysis were: Process of registration of the CAPS procedures, the Unique Therapeutic Project in quotation marks and Qualification of the PTS through the understanding of the records and and the opposite also. The results showed that the professionals did not know the instruments of records of CAPS procedures, the meaning of the names of the procedures, the management and purposes of the records and the importance of the data as the driver of information for work and service management. Two situations on the quality of records were evidenced that the data were underreported or reflected the inexistence of psychosocial actions. It was perceived the need of investment in the training of the professionals with focus on the records management and through the systematization of PTS. The Permanent Health Education strategy expanded the repertoire of information about CAPS procedures and was evaluated positively by enabling a better understanding of the records, deconstruction of the idea of association of registration for financial transfer, use of the list of procedures as a care line for elaboration of more robust PTS and revision of Institutional Therapeutic Projects. The incompleteness and underreporting of the data do not depict what the teams in the CAPS are developing and, therefore, the conclusion that the analysis of the data generated through them does not coincide with the reality of the services. It is important to emphasize the importance of the process of permanent education as a way of giving priority to more meaningful learning practices involving the participants in the process of change and thus highlighting the psychosocial practices by recording the actions developed in the CAPS or other devices in the territory. This evidence is fundamental for the technical and political defense of the model of psychosocial care in force in the country.